Eczane eczacılarının diyabet hastalarının tedavisi, izlemi ve eğitimindeki rollerinin incelenmesi: İstanbul Zeytinburnu örneği / Evaluation of the role of community pharmacists in the treatment, follow-up and education of diabetic patients: İstanbul Zeytinburnu case - MERCAN, Sümeyye (Bezmialem Vakıf University, 2018)
Background and Objective: In many countries, it becomes increasingly common to extend the practice role of community pharmacists towards public health activities. In order to inform policy makers, this study aimed to examine the role of pharmacists in the tertiary prevention of diabetic patients contactingı their pharmacies. Materials and Methods: In this mixed methods research, concurrent triangulation and concurrent transformative designs were combined. Data were collected face-to-face through a questionnaire in the descriptive quantitative study and through semi-structured interviews in the qualitative study. The data were blended during the interpretation stage and triangulation was used in the discussion of the findings. Results: The majority of the pharmacists (98.7%) believe that they should undertake roles in preventive health and health promotion. Although not systematically, the pharmacists have undertaken a number preventive services for diabetics, limited with their own knowledge, concerns and facilities. The main motivators for offering such services were the needs of patients and perceiving the task as pharmacist's own responsibility; the main barriers were lack of time, excessive workload and absence of a particular system for the implementation such activities. Professional development training, establisment of a system, allocation of resources and collaboration with other health professionals were suggested as the preconditions for pharmacists be involved in preventive activities. Conclusions: The research indicates that many pharmacists undertake roles in public health for diabetic patients and that these roles could be developed further with appropriate support. The findings provide a wide-scale evaluation of the subject through mixed research methodology and also offer important clues for future policies. Keywords: Community pharmacist; diabetes mellitus; mixed research methodology; preventive care; health promotion

{{abstract}}
Thesis (Medical)--Bezmialem Vakıf University, Faculty of Medicine, Department of Public Health, Istanbul, 2018
Keywords: Halk Sağlığı = Public Health; Diabetes mellitus = Diabetes mellitus; Eczacılar = Pharmacists; Eczacılık = Pharmacy; Hasta eğitimi = Patient education; Koruyucu hekimlik = Preventive medicine; Sağlık hizmetleri = Health services; Sağlık hizmetleri araştırmaları = Health services research; Sağlığın geliştirilmesi = Health promotion; Tedavi = Treatment; İstanbul-Zeytinburnu